A Study on Mass Media Preferences and Constraints Faces by the Farmers in Imphal East District Manipur - Singh, Baldev; Prasad, Angad; Chanu, Ngangom Diyarani; Amulya, R.; S., Yuvaraj (International Journal of Economic Plants, 2024)
A research study was conducted during March–April, 2023 at Imphal East, Manipur, India to gain insights into the preferences and constraints of farmers concerning their utilization of mass media. Two blocks were select randomly and from each block two villages were selected randomly; a total 120 respondents were interviewed through structured scheduled. Mean, frequency, percentage and garret ranking method were used to analysis the data and to find out the appropriate result. The outcomes illuminated that, among the farmers, mobile phones emerged as the most favored mass media, trailed by television, radio, newspapers, and agricultural magazines. The major constraints faced by farmers in the case of television were a lack of market availability of suggested inputs (59.16%), a lack of use of a complex technical word (44.16%) in radio, a lack of use of a complex technical word (46.66%) in newspapers, no one subscribe to any farm magazine (94.16%) in farm magazines, and a lack of awareness of mobile applications related to agriculture (56.66%) on mobile phones. This study underscores the pivotal role of mass media in rural areas and highlights the challenges tied to specific mass media.